211k views
5 votes
Simplify


- 2i √( - 12)
Enter your answer in simplest radical form, in the box.


User Mrueg
by
4.7k points

1 Answer

5 votes

Answer:
4√(3)

Explanation:

For this exercise it is important to remember the following:


i=√(-1) \\\\i^2=-1

Given the following expression:


-2i√(-12)

You can notice that the radicand (the number inside the square root) is negative. Therefore, in order to simplify the expression, you need to follow these steps:

1. Replace
√(-1) with
i and simplify:


(-2i)(i)√(12)=-2i^2√(12)=-2(-1)√(12)=2√(12)

2. Descompose 12 into its prime factors:


12=2*2*3=2^2*3

3. Substitute into the expression:


=2√(2^2*3)

4. Since
\sqrt[n]{a^n}=a, you can simplify it:


=(2)(2)√(3)=4√(3)

User UTubeFan
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.